Pemetaan Bibliometrik Penelitian Wakaf Uang: Tren, Tema, dan Arah Penelitian - Muhammad Farhan Aqila; Ramdani Ramdani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the development and direction of research on cash waqf through digital platforms using bibliometric methods with descriptive qualitative approaches. Data obtained from the Scopus database, covering 771 publications up to October 2025, were processed using VOSviewer to map publication trends, collaboration networks, and research themes. The results show a significant increase in digital cash waqf research since 2015, with contributions from researchers from Indonesia and Malaysia dominating, confirming Southeast Asia as a hub for modern waqf studies. Thematic analysis identified four main focuses: governance, sharia regulation, financial technology innovation, trust and transparency, and socio-economic impact. The research evolution is divided into three phases, from conceptual studies to waqf integration and digitalization. Theoretically, this study strengthens the concept of Islamic social finance through digitalization, while practically providing policy recommendations and technological innovations such as blockchain and sharia fintech, opening new directions for future research on the integration of blockchain technology, artificial intelligence, and Islamic financial systems for sustainable cash waqf management.